The Influence of Visual Thinking Strategy In Augmented Reality (ViTSAR) to Improve Students' Visual Literacy Skills on Magnetic Field Material - Permana, Firman; Guntara, Yudi; Saefullah, Asep (Universitas Islam Negeri Ar-Raniry, 2025)
he purpose of this study was to examine the effect of ViTSAR inimproving students' Visual Literacy Skills on magnetic field material. Theresearch location was at SMAN 1 Baros in the 2024/2025 academic year. Theresearch method used was a quantitative research method. This type ofresearch is a quasi-experiment with a pretest-posttest nonequivalent controlgroup design. The population of the study was all grade XII MIPA studentsat SMAN 1 Baros. The sample of this study was 32 grade XII MIPA 1 studentsas the experimental class and 32 grade XII MIPA 2 students as the controlclass. The instruments used in this study were Visual Literacy Skills testquestions and student response questionnaires. The results of the t-testobtained a significance of 0.001, meaning that the t value was significant (p =0.001 <0.005), so there was an influence of the Visual Thinking Strategy inAugmented Reality (ViTSAR) learning media to improve Visual LiteracySkills on Magnetic Field material. The results of students' responses tolearning using ViTSAR media were very good, obtaining results of 80% sothat this method can improve students' Visual Literacy Skills, especially inlearning physics on magnetic field material.